2003
DOI: 10.1108/02683940310484044
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of adult wellbeing: adolescent religiosity and health

Abstract: An extant of literature has demonstrated an apparent connection between religiosity and physical and psychological health, yet there is a scarcity of studies focussing on the impact of religion on health among children and adolescents. The current study examined associations between self‐report data on self‐image, physical and psychological health and death‐related cognitions in a large representative sample of German high‐school students. Almost 1,000 German adolescents (aged 14‐18 years) were administered a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…In terms of the characteristics of those youth that attend religious activities, previous studies have found that female teens attend more religious activities than males (Francis, 2000;Martin, Kirkcaldy, & Siefen, 2003;Office of Applied Studies, 2004;Steinman & Zimmerman, 2004). The present study did not find any gender differences; however, this may be due to the younger age of this sample (mean age 11.5 years) compared to the sample used by others (primarily adolescent).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In terms of the characteristics of those youth that attend religious activities, previous studies have found that female teens attend more religious activities than males (Francis, 2000;Martin, Kirkcaldy, & Siefen, 2003;Office of Applied Studies, 2004;Steinman & Zimmerman, 2004). The present study did not find any gender differences; however, this may be due to the younger age of this sample (mean age 11.5 years) compared to the sample used by others (primarily adolescent).…”
Section: Discussioncontrasting
confidence: 78%
“…However, only 15% met with a spiritual leader to aid in coping (Larson & Larson, 2003). Compared to other studies of youth, in general, these youth were more frequent participants in religious activities (Christian & Barbarin, 2001;Martin, Kirkcaldy, & Siefen, 2003). Specifically, a greater proportion of youth in this sample report participating in religious activities than youth of other samples.…”
Section: Discussionmentioning
confidence: 61%
“…Public religious activity (e.g., church attendance) also predicts well-being (Ferriss 2000;French and Joseph 1999;Laurencelle et al 2002;Martin et al 2003;Maselko and Kuzansky 2006)-however, the direction of causality is not obvious (i.e., healthier believers are more able to attend services). Furthermore, positive (e.g., acceptance and forgiveness, see Pargament et al 2004), but not negative religious coping (e.g., discontent, pleading, passivity/deferral etc.…”
Section: A Brief Review Of Evidence Supporting the Belief-as-benefit mentioning
confidence: 97%
“…Corbin, Lindey, Welk and Corbin (2002) describe wellness as a person's state of well-being that contributes to an improved quality of life. In addition, the literature uses the terms wellness and well-being interchangeably (Korhonen et al, 1998;Martin, Kirkcaldy & Siefen, 2003). This absence of a universal definition, and confusion about a preferred term to describe wellness, pose great difficulties to developing guidelines for good wellness practices in organisations.…”
Section: Background To the Studymentioning
confidence: 99%